Features of the historical memory of students of Russian megacities - I. A. Yurasov; M. A. Tanina; V. A. Yudina (Вестник университета, 2021)
In the course of sociological analysis, linguistic models of students’ historical memory, events and historical figures were identified, that represent, in the opinion of young people, the “political evil” and the “political good” in Russian history. The students identified serfdom, “Stalinist repressions”, the famine of the 1920s and 1940s and the wars in Afghanistan and Chechnya as “political evil”. The “political good” – the victories in the Patriotic War of 1812, the Great Patriotic War, the flight to space, the 1980 and 2014 Olympics. The author’s sociological studies of the largest Russian megalopolises have revealed the complexity and inconsistency of the historical memory of student youth. The study established the adherence of student youth to liberal ideology, a shallow awareness of the life of their family, their kin in earlier periods of Russian history, from pre-revolutionary times to the lives of their relatives in the 20-40s of the XX century, the association of “political good” with the achievements of our country and the association of “political evil” with defeats and reforms.